Implementasi Studi Islam Interdisipliner dalam Pendidikan Islam Berbasis Moderasi Beragama - rozi, Fahrur; Qomar, Mujamil; Sokip, Sokip (Edukais : Jurnal Pemikiran Keislaman, 2025)
This study was conducted to discuss in depth the contribution of interdisciplinary Islamic studies in Islamic education based on religious moderation. Building Islamic education based on religious moderation through interdisciplinary Islamic studies is a bond that cannot be separated. This research is a type of library research because it focuses on data collected from library sources. The research results show that religious moderation and scientific integration in interdisciplinary Islamic studies form an inseparable link. Moderation in the modern era still needs to be done, considering that Indonesia’s richness and diversity still need to be preserved even in the midst of the modern era. Efforts to build moderation in religion can start by instilling a mentality to continue to prioritize justice, not be hypocritical, adapt and live in solidarity with all levels of society. A strong balance in the development of Islam requires strengthening the logical foundation in accordance with Islamic teachings. The practice of religious moderation can start from the lowest level, such as family education, or from the highest level.